The broken heavens - Hurley, Kameron (Hurley, Kameron. Worldbreaker saga., 2020)
The Dhai nation has broken apart under the onslaught of the Tai Mora, invaders from a parallel world. With the Dhai in retreat, Kirana, leader of the Tai Mora, establishes a base in Oma's temple and instructs her astrologers to discover how they can use the ancient holy place to close the way between worlds. With the connected worlds ravaged by war and Oma ascendant, only one world can survive. Who will be sacrificed, and who will be saved, when the heavens finally break?